A Multidisciplinary Approach to Islamic Religious Education: Psychological, Political, and Legal Perspectives - Adam Adam; Rizki Al-Gifari; Andi Andi; Wahyu Mulyadi; Ilham Ilham (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine and describe a multidisciplinary framework for Islamic Religious Education through the integration of psychological, political, and legal approaches. The psychological approach focuses on students' motivation, development, and personality as a basis for strengthening the process of internalizing values. The political approach examines the influence of educational policies, state ideology, and the dynamics of pluralism in directing the orientation of Islamic Religious Education learning. Meanwhile, the legal approach is analyzed to understand the normative and regulatory foundations that support the implementation of Islamic Religious Education in Indonesia. This study uses library research. Data were collected through a literature search of journals and books. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that the integration of these three approaches produces a more comprehensive, adaptive, and contextual framework for Islamic Religious Education. The psychological approach provides effectiveness in character-based learning, the political approach strengthens the relevance of Islamic Religious Education in the national education system, and the legal approach ensures the legitimacy and direction of religious value development. Overall, multidisciplinary Islamic Religious Education is able to shape religious students.